Simultaneous access to different types of volume changes and the degree of cure during isothermal polymerization of polymer networks - Andreas Klingler; Maurice Gilberg; Bernd Wetzel; Jan-Kristian Krüger (eXPRESS Polymer Letters)
The current paper addresses the network-formation process of an epoxy polymer focussing on transition phenomena like the percolation threshold and the chemically induced glass transition. Based on a single type of measurement, different kinds of volume changes are used as sensitive probes to the morphological changes accompanying the polymerization process. Thereby, the rather new experimental technique of ‘Temperature Modulated Optical Refractometry’ (TMOR) allows to simultaneously obtain not only the volume shrinkage and the accompanying dynamic thermal volume expansion in the course of polymerization, but also the chemical turnover as a function of the refractive index. In order to test the applicability of the refractive index as a reasonable quantity to substitute respective infrared spectroscopy (IR) measurements, the network-formation is induced by homopolymerization reactions to specifically limit the degree of cure to a single spectral IR component. This countercheck is performed using IR by attenuated total reflection (ATR). Whereas the chemical-induced glass transition is clearly evidenced by the different kinds of volume changes, the percolation transition does not couple to these properties. However, the transition to the glassy state is highly variable and leads to large differences of the macromolecular-induced morphologies.